Changes in the survival of older patients with hematologic malignancies in the early 21st century. Issue 13 (10th May 2016) - Pulte, Dianne; Jansen, Lina; Castro, Felipe A.; Brenner, Hermann
Abstract : BACKGROUND: Survival for patients with hematologic malignancies has improved during the early 21st century. However, it is unclear whether older patients have benefited to the same extent as younger patients. This study examines changes in survival for older patients with the 7 most common hematologic malignancies. METHODS: Period analysis was used to examine survival for patients who were 65 years old or older and were diagnosed with a common hematologic malignancy between 1992 and 2012 with data from the Surveillance, Epidemiology, and End Results database. RESULTS: Five‐year relative survival increased for older patients with hematologic malignancies with the partial exception of acute myelogenous leukemia, for which no change in survival was seen for patients who were 75 years old or older. Patients with chronic lymphocytic leukemia and non‐Hodgkin lymphoma, including the oldest patients, had especially strong improvements, with increases in 5‐year relative survival for patients who were 85 years old or older of 31.5% and 39.6%, respectively, between 1997‐2000 and 2009‐2012. CONCLUSIONS: Despite these increases, survival rates did not reach those observed for patients aged 50 to 59 years for any hematologic malignancy. Newer therapies and a better understanding of how to treat older patients have led to increased survival expectations for older patients with most hematologic malignancies, but an age‐related survival disparity persists. Cancer 2016;122:2031–40 . © 2016 American Cancer Society . Abstract : Five‐year relative survival has increased for older patients in the early 21st century for most common hematologic malignancies, but it continues to be lower than that for younger patients. This age‐related disparity is decreasing for lymphomas.